Reasons for the increase in cyber attacks: analysis of technical and non-technical factors - A. V. Vasilyev (Системный анализ и прикладная информатика)
This article presents an analysis of both technical and non-technical factors contributing to the growth in volume and diversity of cyber attacks. Social interaction on the Internet contributes to the increased frequency of cyber attacks and exacerbates destructive consequences that extend beyond technical aspects, impacting societal and personal realms. Software errors, vulnerabilities, and deficiencies in network protocols pose a persistent security threat, particularly amidst the rising number of connected devices and the complexity of managing critical systems. The dynamic nature of attacks and evolving penetration methods make cyber threats highly adaptable to the conditions of the modern network environment.Furthermore, the expanded use of social media and the virtualization of social life bring increased comfort but also provide fertile ground for cyber attacks, amplifying the volume of accessible information for potential malicious actors. The heightened technical proficiency of attackers equips them with new tools for breaching digital security. Concurrently, inadequate awareness and careless user behavior online jeopardize the protection of personal and confidential data.This work demonstrates that cyber risks escalate due to both ongoing technological changes and human actions. Understanding the dynamics of these factors becomes critically important for developing more effective measures to safeguard the digital environment.